Genetic Stability And Hormone–Ros Regulation In High-Efficiency In Vitro Micropropagation Of Euodia - Zukhra, Abdurakhmanova; Kushiev, Khabibjan; Jumanov, Utkirjon; Shernazarova, Sanobar; Sardor, Obloberdiyev; Dilafruz, Xakimova; Nazira, Vafoyeva; Manzura, Moʻminova; Aziza, Akhmedova (International Journal of Aquatic Research and Environmental Studies, 2026)
Efficient micropropagation of woody medicinal species requires the integration of morphogenetic efficiency, genetic stability, and physiological resilience. This study develops a comprehensive in vitro propagation system for Euodia based on hormonal optimization, molecular validation, and stress-responsive physiological analysis. Apical explants cultured on Murashige and Skoog (MS) medium supplemented with 1.5 mg L⁻¹ 6 benzylaminopurine (BAP) and 0.5 mg L⁻¹ indole-3-acetic acid (IAA) exhibited the highest regeneration efficiency (85 ± 3.2%) and callus formation (70 ± 2.8%), significantly outperforming other explant types (p < 0.001). Genetic fidelity analysis using SSR markers revealed high clonal stability (98–100% similarity), confirming the absence of somaclonal variation. Gene expression profiling demonstrated significant upregulation of auxin-responsive genes (ARF: 2.3-fold; AUX/IAA: 1.9-fold) and antioxidant genes (SOD: 2.1-fold; CAT: 1.8-fold), indicating coordinated activation of hormonal and oxidative signaling pathways. These molecular responses were supported by enhanced physiological parameters, including increased activities of SOD (+42%), CAT (+38%), and POD (+35%), elevated proline accumulation (+55%), and reduced lipid peroxidation (MDA −28%). The acclimatization success rate reached 90 ± 2.1%, confirming the functional viability of regenerated plantlets under ex vitro conditions. Collectively, these results provide the first integrative evidence that Euodia regeneration is regulated by a hormone–ROS interaction network coupled with high genetic stability, establishing a robust and scalable platform for its application in sustainable agriculture and ecological restoration.